Strategi Pemasaran Agen PT Prudential Dalam Mmpertahankan Loyalitas Nasabah Prulink Syariah - Indri Anggraini Putri; Nuri Aslami (LPPM IAI Nasional Laa Roiba Bogor, 2021)
This review expects to investigate the advertising procedure of PT Prudential's representatives in keeping up with the devotion of prulink sharia clients. This examination technique utilizes engaging subjective strategy with information investigation, in particular information assortment, interviews, information show and end drawing. The consequences of the review propose that in keeping up with client unwaveringness the advertising techniques of PT Prudential's representatives are right off the bat by giving intermittent data to clients, besides assembling individual associations with clients. Considering that there are as yet many individuals who don't comprehend the significance of protection, it is a chance for advertisers to give protection instruction to the public so they can grow the sharia protection business. Watchwords: methodology, client devotion, specialist.